2014
DOI: 10.2147/cia.s60669
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of antihypertensive medications on bone mineral density in men older than 55 years

Abstract: IntroductionIn this study, we investigated the effects of long-term antihypertensive treatment with calcium channel blockers or beta blockers on the bone mineral density of maxilla, as determined by cone-beam computed tomography (CBCT).Material and methodsThis retrospective study was conducted on CBCT images of men older than 55 years who had received different dental indications. Data were grouped into three categories according to the antihypertensive medication history of the patients: group A included pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…CBCT is currently used to measure preoperative BMD for dental implant placement 25 or to assess for medication-induced osteoporosis. 26 BMD, as measured by dual-energy X-ray absorptiometry is termed areal bone mineral density (aBMD), and racial differences in aBMD have been useful measures of relative bone strength, but the studies using these measurements appear to have focused on the female vertebrae and femora. Such studies have shown that African Americans have the greatest aBMD, followed by whites, Hispanics, and then Native Americans.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT is currently used to measure preoperative BMD for dental implant placement 25 or to assess for medication-induced osteoporosis. 26 BMD, as measured by dual-energy X-ray absorptiometry is termed areal bone mineral density (aBMD), and racial differences in aBMD have been useful measures of relative bone strength, but the studies using these measurements appear to have focused on the female vertebrae and femora. Such studies have shown that African Americans have the greatest aBMD, followed by whites, Hispanics, and then Native Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium channels, which are in charge of calcium transportation into and out of cells and organelles, play an important role in aging (Surmeier, ; Warnier et al, ). In terms of bone aging, numerous studies have indicated the relationship between disruption of calcium channels and age‐related bone mass loss (Agacayak et al, ; Shimizu et al, ). There are several kinds of calcium channels, among which voltage‐gated Ca 2+ channels (VGCCs) are important components.…”
Section: Introductionmentioning
confidence: 99%
“…Сканы были разделены на три группы в зависимости от типа кардиологического препарата, который пациенты принимали не менее 5 лет: 1 группа -БАБ, 2 группа -АК, 3 -пациенты, не принимавшие сердечно-сосудистые препараты. Объемная МПК у пациентов, принимающих длительно БАБ, была значимо выше, чем в группах АК и контрольной, в связи с чем авторы сделали вывод, что БАБ предпочтительней использовать у пациентов с АГ и высоким риском переломов, связанных с хрупкостью костной ткани [51]. В то же время нет исследований, подтверждающих строгую связь между локальным остеопорозом челюсти и системным остеопорозом.…”
Section: антагонисты кальция (блокаторы кальциевых каналов)unclassified